Spatial control over catalyst positioning on biodegradable polymeric nanomotors - B. Jelle Toebes (Nature Portfolio, 2019)
Multiple nanomotors for application in various fields have been fabricated, but so far only relatively simple designs for synthetic nanomotors are reported. Here, the authors report on a biodegradable polymeric nanomotor and demonstrate spatial control for catalyst positioning.